Risk factors for breast cancer in Iranian women: a case-control study - Abbasi, Sakineh; Azimi, Cyrus; Othman, Fauziah; Einollahi, Nahid; Dashti, Nasrin; Nabatchian, Fariba; Ismail, Patimah (Academic Journals, 2009)
The objective of the present study was to investigate risk factors for breast cancer in Iranian women. A case-control study was conducted from April 2004 to May 2007 in Tehran, Iran. Demographical data and risk factor related information were collected using a short structured questionnaire. In all, 150 women with breast cancer and 147 control women were interviewed. In multivariate analysis, only body mass index or BMI age at menarche, age at marriage, race, ABO and Rh blood groups and family history of breast cancer were associated with significantly increased risk for breast cancer (P<0.05). The findings of the present study suggest that family history and marital status may have an impact on the incidence of breast cancer in Iranian women.